ENGLISH TEACHERS’ AND STUDENTS’ PERCEPTION TOWARDS IMPLEMENTATION OF KURIKULUM MERDEKA BELAJAR AT SECONDARY SCHOOL - Zebua, Sovi Septia Diana; Zai , Irene Netalis Mawati Zai; Gea , Faeriani; Harita , Epifania Anggun Yunita; Halawa, Arif Wahyu Tomosa; Waruwu, Pujawati (LPPM Universitas Harapan Bangsa, 2024)
This study aims to explore teachers' and students' perceptions of Kurikulum Merdeka Belajar in English language subjects in secondary schools. Using a descriptive qualitative approach, this study used questionnaires and interviews as data collection instruments. This study reveals English teachers' and students' perceptions of the implementation of Kurikulum Merdeka Belajar belajar at secondary schools including the concept of Kurikulum Merdeka belajar project-based learning, teaching modules, and assessment, as well as how students perceive the implementation of Kurikulum Merdeka Belajar. The research findings showed positive and negative perceptions of both teachers and students. The positive value for a teacher is that they are free to provide material to students relevant to their respective needs while the negative value is the lack of school facilities that hamper the creativity of teachers in making teaching materials. The positive value for students is that they are more free to express their opinions and be creative according to their respective talents through p5 activities, while the negative value is their challenge in adjusting each new subject listed in Kurikulum Merdeka Belajar.